ANALYSIS OF CORRUPTION AND ITS IMPACT ON NATIONAL DEVELOPMENT - Fauzanna Zamalika (Academic Solution Publisher, 2025)
Corruption is a common enemy that causes losses to the state through the obstruction of the development process, increasing social inequality, weakening public trust, and inefficient management of resources. This article thoroughly explores the issue of corruption and its impact on national development. By presenting a thorough analysis of the factors affecting the spread and intensity of corruption and its consequences in various sectors of the development process, this article highlights the complexity of the problem of corruption within the framework of national development. This research is a normative legal research, and the type of data used is qualitative data. The negative impacts of corruption not only include economic losses, but also damage social order, reduce public trust in the government, and hinder sustainable economic growth. This research aims to comprehensively examine the dynamics of corruption in Indonesia, with an emphasis on the legal and social efforts that have been made to address this problem. Through an in-depth understanding of the phenomenon of corruption, it is hoped that we can formulate effective strategies to combat corruption and promote sustainable and inclusive national development